2022
DOI: 10.2196/33458
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Heart Rate and Heart Rate Variability During Pregnancy and the 3-Month Postpartum Period: Continuous Monitoring in a Free-living Context

Abstract: Background Heart rate variability (HRV) is a noninvasive method that reflects the regulation of the autonomic nervous system. Altered HRV is associated with adverse mental or physical health complications. The autonomic nervous system also has a central role in physiological adaption during pregnancy, causing normal changes in HRV. Objective The aim of this study was to assess trends in heart rate (HR) and HRV parameters as a noninvasive method for remo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…In particular, aggregate nighttime HR and RR were higher among individuals in pregnancy related-condition groups compared to healthy individuals -a difference that was observed early in pregnancy through birth, while HRV steadily decreased with gestational age, but showed an inflection at approximately nine weeks leading up to delivery. This phenomenon, that could reflect an individual's physiological readiness for delivery, has been observed in the aggregate among other studies [18,23,26]. However, at the n-of-1 level, this aggregate trend is highly heterogeneous, even among healthy pregnant individuals.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In particular, aggregate nighttime HR and RR were higher among individuals in pregnancy related-condition groups compared to healthy individuals -a difference that was observed early in pregnancy through birth, while HRV steadily decreased with gestational age, but showed an inflection at approximately nine weeks leading up to delivery. This phenomenon, that could reflect an individual's physiological readiness for delivery, has been observed in the aggregate among other studies [18,23,26]. However, at the n-of-1 level, this aggregate trend is highly heterogeneous, even among healthy pregnant individuals.…”
Section: Discussionsupporting
confidence: 63%
“…With the ubiquity of the smartphone [15], and the increasing popularity of wearable smart devices [16] such as the smartwatch and the smart ring, the use of such tools for monitoring pregnancy-related signs and symptoms and greatly transforming current knowledge of this important metamorphosis is a potential reality. While the body of research involving personal DHTs in pregnancy is small, a number of small preliminary studies have shown potential utility in using wearables for tracking activity, sleep, and physiologic metrics such as HR and HRV as predictors of pregnancy-related outcomes such as preterm birth and delivery readiness [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…We used data from late pregnancy (gestational week 36) and 12 weeks postpartum for loneliness prediction. However, it is known that physiological health parameters such as HRV and physical activity change during pregnancy and the postpartum period [43, 44], e.g., physical activity decreases during pregnancy. Generalizing our predictive models to the whole pregnancy requires using data from additional weeks during pregnancy and the postpartum period.…”
Section: Discussionmentioning
confidence: 99%
“…Final multivariable HRV models were random‐intercept restricted maximum likelihood mixed models that included each of the substance use reports (alcohol, nicotine, and marijuana). Based on the literature, models were further adjusted for subject (level‐2) factors of pregnancy status (pregnant vs. postpartum) and age (Sarhaddi et al, 2022; Shaffer & Ginsberg, 2017). Potential interaction effects between pregnancy status and reports of substance use were examined, but were not significant.…”
Section: Methodsmentioning
confidence: 99%